2003
DOI: 10.1086/367591
|View full text |Cite
|
Sign up to set email alerts
|

The Relative Importance of Life‐History Variables to Population Growth Rate in Mammals: Cole’s Prediction Revisited

Abstract: The relative importance of life-history variables to population growth rate (lambda) has substantial consequences for the study of life-history evolution and for the dynamics of biological populations. Using life-history data for 142 natural populations of mammals, we estimated the elasticity of lambda to changes in age at maturity (alpha), age at last reproduction (omega), juvenile survival (Pj), adult survival (Pa), and fertility (F). Elasticities were then used to quantify the relative importance of alpha, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
210
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(228 citation statements)
references
References 148 publications
(134 reference statements)
16
210
0
2
Order By: Relevance
“…Nevertheless, attributing large reductions in rabbit populations to an apex predator appears to contradict ecological theory. Reproductive parameters, not survival rates, should most influence population growth of fecund, early-maturing species like marsh rabbits [12]. One explanation for this contradiction in theory is that marsh rabbits were naive to predation by an introduced predator such as the Burmese python.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, attributing large reductions in rabbit populations to an apex predator appears to contradict ecological theory. Reproductive parameters, not survival rates, should most influence population growth of fecund, early-maturing species like marsh rabbits [12]. One explanation for this contradiction in theory is that marsh rabbits were naive to predation by an introduced predator such as the Burmese python.…”
Section: Discussionmentioning
confidence: 99%
“…Introduced predators, including snakes, have reduced or eliminated fauna on islands [9][10][11], yet there are no accounts of a lone introduced apex predator (apart from humans) removing a functionally diverse, continental mammal community. Additionally, ecological theory provides little support for the hypothesis that an apex predator could extirpate small, broadly dispersed, fecund, generalist herbivores [12][13][14]. To test the hypothesis that pythons are driving the decline of mammal populations, we experimentally manipulated marsh rabbit (Sylvilagus palustris) populations in ENP.…”
Section: Introductionmentioning
confidence: 99%
“…Most animal and plant species can be found in a wide range of ecologically distinct habitats, and as a result, individuals of the same species may experience substantial variation in demographic rates, such as survival, growth, and fecundity. These demographic heterogeneities between individuals or groups of individuals can have considerable population dynamical consequences and can generate evolutionary change (e.g., Rees et al 2000;Saether et al 2002;Oli and Dobson 2003;Pfister and Stevens 2003;Rose et al 2005;Benton et al 2006;Burd et al 2006;Coulson et al 2006;Metcalf and Pavard 2007;Sletvold and Grindeland 2007).…”
mentioning
confidence: 99%
“…First, our graphical analyses revealed that life-history speed can be shaped by both the temporal frequency of favorable environment states and the patterning of environment states through time. In constant environments, life-history variables such as age at maturity and generation time provide a measure of the position of a given population along the slow-tofast life-history continuum (Charlesworth 1994;Heppell et al 2000;Oli and Dobson 2003;Gaillard et al 2005;Stahl and Oli 2006). Our analysis revealed that in stochastic environments, lifetime reproductive success and population growth rate are reliable proxies for life-history speed.…”
Section: Discussionmentioning
confidence: 86%